Transient application of foliar urea with N-n-Butyl thiophosphoric triamide on N metabolism of pineapple under controlled condition - Haque, Mohammad Amdadul; Sakimin, Siti Zaharah; Md Jaafar, Noraini; Ding, Phebe; Sarker, Babul Chandra; Islam, Mahammad Shariful; Yusop, Mohd Khanif (Elsevier, 2022)
Traditional fertilization and the loss of Nitrogen (N) is a common phenomenon in agriculture. Application of urea with urease inhibitor is an alteration measure of urea hydrolysis and N metabolism. Hence, the objective of this study was to determine the short-term foliar application effect of N-(n‑butyl) thiophosphoric triamide (NBPT) on N metabolism, physiological and biochemical changes in the pineapple plant. At 4 month after planting (MAP), 1% urea (Urea) and 1% urea with NBPT (NLU) were applied. Data on urease enzyme activity, internal urea content, inorganic N [ammonium (NH4+) and nitrate (NO3−)], amino acids, total soluble protein, NBPT content, lipid peroxidase (MDA) activity, and electrolyte leakage were recorded for 10 days after treatment (DAT). The results indicated that the NBPT was taken up by the plant, thereby a clear inhibition of the urease activity was observed in pineapple leaf. A higher amount of urea content and a lower amount of NH4+ content in the leaf were the evidence of hydrolysis inhibition by NBPT. Consequently, the contents of amino acid and protein were diminished upon NBPT treatment which demonstrated a change in N metabolism. In addition, amino acid composition demonstrated that amide forms of amino acids were the major components of the decreased amino acid pool. In conclusion, lower MDA activity and electrolyte leakage were also observed under NBPT treated plants indicate that NBPT could release abiotic stress to some extent by protecting the cell wall from damage.